2004
DOI: 10.1111/j.1444-2906.2004.00824.x
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distribution and feeding habits of the shrimp Crangon uritai as a predator on larval and juvenile marbled sole Pleuronectes yokohamae

Abstract: To examine predation on larval and juvenile Pleuronectes yokohamaeby Crangon uritai, the spatial distribution and feeding habits of C. uritai were studied.C. uritai fed on various prey, including P. yokohamae. Density-dependent predation on juvenile Crangon spp., larval and juvenile gobiid fish Chaenogobius heptacanthus, mysids, and gammarids was observed. The abundance of alternative prey might therefore play an important role in reducing the pressure of predation on P.yokohamae. In each year, C. uritai migra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 32 publications
0
17
0
Order By: Relevance
“…It is possible that the reproductive strategy of marbled sole of the population studied here is a response to poor larval growth conditions and large eggs in the early spawning period mitigate recruitment failure. In Hakodate Bay, water temperature and densities of copepod nauplii and rotifers (the initial prey items for marbled sole larvae) are low in March and increase in April (Nakagami, 2001;Nakaya et al 2004). It has been shown that smaller larvae may be disadvantaged in terms of food availability and growth under conditions of low prey abundance or inadequate temperature in the wild (Hutchings, 1991;Benoît and Pepin, 1999;Rideout et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that the reproductive strategy of marbled sole of the population studied here is a response to poor larval growth conditions and large eggs in the early spawning period mitigate recruitment failure. In Hakodate Bay, water temperature and densities of copepod nauplii and rotifers (the initial prey items for marbled sole larvae) are low in March and increase in April (Nakagami, 2001;Nakaya et al 2004). It has been shown that smaller larvae may be disadvantaged in terms of food availability and growth under conditions of low prey abundance or inadequate temperature in the wild (Hutchings, 1991;Benoît and Pepin, 1999;Rideout et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, marbled sole juveniles that were larger than the maximum vulnerable size for sand shrimp predation were assumed to get out of the phase that predation mortality was relatively high. The maximum ratio of body length of predated marbled sole to that of C. uritai is 0.32 [8], and the maximum body length of C. uritai has been reported to be 48. were omitted from the analysis. Data were expressed as the percentage frequency of occurrence (F%, the percentage of larvae that consumed a particular type of prey), percentage in number (N%, the percentage of each prey type consumed to the total number of prey items), feeding intensity (FI, the ratio of the total number of each prey type to the total number of larvae examined), and the feeding rate (the proportion of larvae with prey to the total number of larvae examined).…”
Section: Sampling and Treatment Of Specimensmentioning
confidence: 99%
“…The sand shrimp C. uritai is a predator of metamorphosing larvae and juveniles [8][9][10]; other demersal predators of them are rare in Hakodate Bay [20]. Therefore, marbled sole juveniles that were larger than the maximum vulnerable size for sand shrimp predation were assumed to get out of the phase that predation mortality was relatively high.…”
Section: Sampling and Treatment Of Specimensmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies have investigated the feeding behavior of crangonid shrimp including C. affinis by Kosaka (1970) and Hong and Oh (1989); C. allmani by Allen (1960); C. crangon by Lloyd and Yonge (1947); Tiews (1970), and Oh et al (2001); C. franciscorum and C. nigricauda by Wahle (1985); C. septemspinosa by Price (1962) and Wilcox and Jeffries (1974); and C. uritai by Nakaya et al (2004). However, despite its ecological and economic importance, there is no information on the diet of C. hakodatei.…”
Section: Introductionmentioning
confidence: 99%